The comparison of color stability between thermoplastic nylon resin and heat-cured acrylic resin after tea-soaking using spectrophotometer - Lestari, Lisa Putri; Usri, Kosterman; Febrida, Renny (Padjadjaran Journal of Dentistry, 2009)
Color stability is one of the denture base material requirement. Nowadays, nylon thermoplastic resin and heat-cured acrylic resin which is used as denture base materials can be changed in colour. One of a colour-changed factor is the tea drinking habit. The objective of this research was to compare the colour stability between nylon thermoplastic resin and heat-cured acrylic resin after soaked in tea. Materials used for the research were nylon thermoplastic resin from Valplast and heat-cured acrylic resin QC-20, with a sample size of 64x(10±0.03)x(2.5±0.03)mm. The sample would be assessed of colour stability after the denture base soaked in tea for 7 days. The colour measurement of each sample was done by spectrophotometer equipment (CIE lab system). Data gathered later on statistically processed with ANOVA testing. The result showed that the comparison ratio of colour stability between nylon thermoplastic resin and heat-cured acrylic resin after soaked in tea was 1.9886:1.1152. The conclusion was that colour stability in the nylon thermoplastic resin was lower than heat-cured acrylic resin after soaked in tea. This result was due to a polymer chain of nylon thermoplastic which was lower than heat-cured acrylic resin and its porosity which was higher, so tea easily soaked into the materials.